The forever mountain [large type] - Dundee, Wayne D. (Dundee, Wayne D. Lone McGantry western, 2023)
"The dying request of an old friend sends former Indian scout Lone McGantry on a perilous journey from the barren Nebraska Sandhills to the ragged, snowy peaks of the Colorado Rockies. Danger dogs his trail right from the start, beginning with a pack of vengeful brothers out for his blood. Along the way, Lone crosses paths with a gang of ruthless robbers and also learns that a bounty placed on his head by a misguided cattle baron is responsible for hired guns swarming the territory in search of collecting the pay-out. The only bright spot in any of this is the companionship of an abandoned Oriental beauty with her own desperate need to reach the mountains. Lone's grudging agreement to escort her adds complications, but it also adds a bittersweet hint of romance he didn't know he was missing."--